1970
DOI: 10.3126/jnps.v28i1.1398
|View full text |Cite
|
Sign up to set email alerts
|

Clinico- Biochemical Profile of Neonatal Seizure

Abstract: Objectives: The present study was undertaken to study the incidence, etiological factor, and days of onset, clinical types and biochemical abnormalities in babies having neonatal seizures. Materials and Methods: This is a retrospective, observational hospital based study. Ninety neonates, who developed seizures before 28 days of life and admitted to neonatal intensive care unit and nursery with neonatal seizure, were evaluated for incidence, etiological factor, clinical types and biochemical abnormalities foun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
15
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 3 publications
6
15
0
Order By: Relevance
“…The most common cause of seizure encountered in this study was birth asphyxia, occurred in 34 (56.67%) cases. Sood et al, 4 Kumar et al, 5 and Shah et al 11 reported birth asphyxia as etiology of seizure was 45.71%, 48.27% and 44% cases respectively which are comparable with the result of present study. Similar observation seen by Mizrahi where HIE as the cause of convulsion in 46% cases 19 .…”
supporting
confidence: 90%
See 3 more Smart Citations
“…The most common cause of seizure encountered in this study was birth asphyxia, occurred in 34 (56.67%) cases. Sood et al, 4 Kumar et al, 5 and Shah et al 11 reported birth asphyxia as etiology of seizure was 45.71%, 48.27% and 44% cases respectively which are comparable with the result of present study. Similar observation seen by Mizrahi where HIE as the cause of convulsion in 46% cases 19 .…”
supporting
confidence: 90%
“…Neonatal seizure is an acute emergency which is responsible for very high morbidity and mortality 10,11 . Neonatal seizure observed more in male patient (61.67%) than female (38.33%) in this study which is consistent with study done by Taksande AM et al 10 showed 66.4% male and 33.6% in female newborn.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is in alignment with published report that the seizures are common in male. 5,6 In male, most common age group was between one to five years followed by six to 12 years. There is report saying that seizures have peak frequency of age at onset in two to five years which is similar to our study.…”
Section: Discussionmentioning
confidence: 99%